Assessment of menstrual hygiene management practices and associated socio-cultural restrictions among adolescent school girls in a rural area of North India - Khan, Zainab; Ahmad, Siraj; Singh, Jai Vir; Dwivedi, Akhilesh Dutta (International Journal Of Community Medicine And Public Health, 2019)
Background: There is inadequate information on menstrual hygiene management practices and socio-cultural restrictions among adolescent girls in developing countries. The objective of the present study was to assess the menstrual hygiene management practices and associated socio-cultural restrictions among adolescent school girls. Methods: This descriptive cross-sectional study was carried out among adolescent school girls 10 to 19 years of age, who had attained menarche, in a rural area of district Barabanki. Total 640 adolescent girls were included in the study, and information was recorded on a predesigned and pretested interview schedule. Relevant statistical analysis was done and significant associations were found. Results: 60.5% of the girls were using sanitary pads, and 71.4% took bath during their periods. 41.3% of the girls used to change pads during schools. Unsatisfactory menstrual hygiene management practices were significantly high among girls who were from lower socioeconomic class (p<0.001) and had illiterate mothers (p<0.001). 82.8% of the girls faced religious restriction. Conclusions: Significant associations were found between menstrual hygiene management practices of adolescent school girls with their mother’s education level and socio economic status. A proper menstrual hygiene management practice is very important for every young girl to lead a healthy life and should be achieved at the beginning of their menarche by enhanced information education and communication (IEC) programmes.